2017
DOI: 10.18632/oncotarget.22553
|View full text |Cite
|
Sign up to set email alerts
|

Selenium against lead-induced apoptosis in chicken nervous tissues via mitochondrial pathway

Abstract: To investigate alleviative effect of selenium (Se) on lead (Pb)-induced apoptosis in chicken nervous tissues, 7-day-old chickens were randomly divided into four groups. The control group was fed a standard diet and drinking water. In the Pb and Se/Pb groups, (CH3OO)2Pb was dissolved in drinking water. In the Se and Se/Pb groups, Na2SeO3 was put into the standard diet. Embryonic neurocytes were divided into the control, Se (containing Na2SeO3), Pb (containing (CH3COO)2Pb), and Se/Pb (containing Na2SeO3 and (CH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…For example, Thangarajan et al (2018) have demonstrated that PbAc intoxication in rats alters Bax/Bcl-2 expression, thereby increasing cytochrome c liberate from the mitochondrial matrix in the brain. Zhu et al (2017) have found that PbAc decreased Bcl-2 protein and mRNA expression, and elevated Bax and caspase-3 protein and mRNA expression, thus inducing cell death in chicken brain tissues and embryonic neurocytes via the mitochondrial pathway. Furthermore, Liu et al (2016) have found that PbAc caused a disruption in the mitochondrial integrity, the discharge of cytochrome c, the activation of caspase-3, and apoptosis in rat proximal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Thangarajan et al (2018) have demonstrated that PbAc intoxication in rats alters Bax/Bcl-2 expression, thereby increasing cytochrome c liberate from the mitochondrial matrix in the brain. Zhu et al (2017) have found that PbAc decreased Bcl-2 protein and mRNA expression, and elevated Bax and caspase-3 protein and mRNA expression, thus inducing cell death in chicken brain tissues and embryonic neurocytes via the mitochondrial pathway. Furthermore, Liu et al (2016) have found that PbAc caused a disruption in the mitochondrial integrity, the discharge of cytochrome c, the activation of caspase-3, and apoptosis in rat proximal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…High dietary fluorine was found to decrease TrxR activity in chicken serum and tissues [238]. Similarly, dietary lead was associated with a decreased TrxR activity in chicken brain [239]. Heat stress was shown to compromise the mitochondrial thioredoxin system including Trx2, TrxR2 and Prx3 in growing chickens and dietary curcumin can mitigate this detrimental effect [240].…”
Section: Nad(p)h Quinone Oxidoreductase-1 Nqo1mentioning
confidence: 98%
“…Moreover, a recent study showed that Pb induces apoptosis via the mitochondria pathway in both chicken brain tissues and embryonic neurocytes. This heavy metal can decrease mRNA and protein expression of Bcl-2 (an anti-apoptotic protein) while increase mRNA and protein expression of p53, Bax, Cyt C, and caspase-3 [ 177 ].…”
Section: Mechanisms Related To Cognitive Impairment Induced By Pb mentioning
confidence: 99%